Peran pola asuh toxic parents terhadap perilaku bullying pada remaja - Pramesti, Nabila Dyah Ayu; Meiyuntariningsih, Tatik; Ramadhani, Hetti Sari (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Abstract Teenagers are expected to be able to complete their developmental tasks well, overcome personal problems and behave according to the values ​​and rules of their surrounding environment. However, adolescence is often a challenging time with significant physical and psychological changes, which can affect their attitudes and behavior. One of the negative behaviors that often occurs among teenagers is bullying. This research aims to determine the relationship between toxic parenting patterns and bullying behavior in junior high school teenagers. This research was conducted at SMP